2021
DOI: 10.3889/oamjms.2021.7157
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Course of Rheumatoid Arthritis in Kazakhstani Patients

Abstract: BACKGROUND: Rheumatoid arthritis (RA) prevalence according to the worldwide epidemiological data varies from 0.4% to 1.3%. The disability and mortality rate in RA is high. RA clinic is various, and compiles from articular and systemic manifestations. AIM: The aim of our study was to investigate the clinical course of RA in Kazakhstani patients living in North region of our country. METHODS: The 81 women at the age of 30–55 years with a verified diagnosis of RA who have lived in Kazakhstan for at least 10 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Consistent with data reported in previous studies on the ACPA-positive RA form, our study identified significant correlations of ACPA presence with X-ray stage, RF, ESR, age of RA onset, VAS, BMI, and Gamma globulin level and is, thus, consistent with a more severe course of the disease in our cohort of RA patients [ 37 , 43 – 45 ]. We further found a significant association of polymorphisms in two genes, FCRL3 rs2317230 and STAT4 rs11889341, with ACPA-positive and ACPA-negative forms of RA, respectively, in Central Asian patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with data reported in previous studies on the ACPA-positive RA form, our study identified significant correlations of ACPA presence with X-ray stage, RF, ESR, age of RA onset, VAS, BMI, and Gamma globulin level and is, thus, consistent with a more severe course of the disease in our cohort of RA patients [ 37 , 43 – 45 ]. We further found a significant association of polymorphisms in two genes, FCRL3 rs2317230 and STAT4 rs11889341, with ACPA-positive and ACPA-negative forms of RA, respectively, in Central Asian patients.…”
Section: Discussionsupporting
confidence: 92%
“…Anti-ACPA-positive and anti-ACPA-negative RA can be regarded as two disease entities with different predisposing factors, etiology, disease severity, prognosis, and presumably pathogenesis [ 35 , 36 ]. Furthermore, the presence of ACPA significantly worsens the course of RA, as the presence of these antibodies is associated with the rapid development of deformities, visceral lesions, and comorbidities and a high risk of death [ 37 39 ]. The presence of these autoantibodies is also associated with an increase in disease activity measured by DAS28, X-ray progression, ultrasound of the joints, and a lower probability of achieving disease remission [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%